Cross-National Comparison of the Relative Size of Lower-Tail and Upper-Tail SES Achievement Gaps - Yuko Nonoyama-Tarumi; Sean F. Reardon (SAGE Publishing, 2024)
Cross-national studies on socioeconomic status (SES) achievement gaps have focused on the size of the gap and given less attention to where in the SES distribution the achievement gap tends to be relatively large within a society, and whether this location varies across countries. We estimate the relative size of achievement gaps between students at the 50th and 10th percentiles versus the 90th and 50th percentiles of SES distribution within a society, using the Organisation for Economic Co-operation and Development (OECD) Programme for International Student Assessment (PISA) data. We find OECD countries vary in the size of the ratio of achievement gaps at lower-tail SES and upper-tail SES. Our multivariate analyses show that the ratio is positively associated with within-country patterns of economic inequality, measured by the ratio of income inequality and the ratio of segregation at lower-tail and upper-tail SES. We do not find evidence of an association between the achievement gap ratio and patterns of educational stratification.